Sistem Informasi Inventory Barang Pada Toko Agen Umi Berbasis Web Menggunakan Metode Prototype - Dhea Amalia Putri; Chrisantus Tristianto (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
In an era where information technology and communication continue to advance, competition in the business world is becoming increasingly intense. Companies must strive and employ strategies to sustain their businesses. Success is closely related to a company's ability to manage inventory effectively to meet customer demand maximally. This research aims to develop a web-based inventory management information system for Toko Agen Umi to facilitate the management of stock data and transactions. The development approach adopted is Prototype. The anticipated outcome of implementing this system analysis is to streamline the creation of Purchase Orders, Delivery Orders, and inventory reports with a user-friendly interface. The application aims to organize inventory management in a more structured, systematic, and computerized manner to prevent calculation errors. It is advised not to adhere strictly to one system to allow for continual learning and development in the process.